(untitled) (Neo Science Peer Reviewed Journal, 2023)
Single network administration refers to the practice of managing all aspects of a network infrastructure from a single centralized location. This method offers numerous benefits in terms of efficiency, cost-effectiveness, and ease of maintenance. By consolidating the administration of multiple networks into one, organizations can streamline their operations and improve overall network performance. This article will explore the advantages of single network administration